Severe Thrombocytopenia As the Onset of Late-onset Systemic Lupus Erythematosus: A Case Report And Literature Review (Revista de Medicina Clinica, 2025)
Systemic lupus erythematosus (SLE) is a chronic, potentially fatal, multisystem, autoimmune disorder that primarily affects women of reproductive age. The late-onset form, which occurs after the age of 50, can have a distinct clinical presentation reflected in differences in gender and ethnicity prevalence, clinical manifestations, organ damage, disease activity, and prognosis. We report the case of an 82-year-old woman with a history of cirrhosis, who presented with lower gastrointestinal bleeding and a progressive decrease in platelet count that could not be explained by her underlying condition. After an exhaustive diagnostic evaluation, late-onset SLE was confirmed. Late-onset SLE is a rare entity, generally with a benign course and lower disease activity. However, it has a lower survival rate due to its association with comorbidities, greater organ damage, ageing and longer exposure to traditional risk factors. A broad differential diagnosis is crucial, including unusual manifestations of rheumatic diseases, when common treatments for comorbidities fail to relieve symptoms in older patients.
Keywords: Systemic Lupus Erythematosus; Anemia; Thrombocytopenia; Autoimmunity